Anodizing of multiphase aluminium alloys in sulfuric acid: in-situ electrochemical behaviour and oxide properties. (1st September 2016) - Veys-Renaux, Delphine; Chahboun, Najat; Rocca, Emmanuel
Abstract: The anodized layer growth in H2 SO4 2 mol L −1 on three different aluminium alloys (1050, 7175, 2618) is investigated by in-situ electrochemical methods and ex-situ characterization techniques. SEM observations of the anodic films indicate that they contain defects related to the size and the composition of the intermetallic phases precipitated within the aluminium matrix. The electrochemical resistances of both the porous and the barrier layer are reduced in presence of defects, depending on their size. In-situ electrochemical measurements enable to monitor the anodizing process. Moreover, the comparison of in-situ and ex-situ electrochemical impedance spectroscopy measurements consistently reveals that the barrier layer is greatly affected by the microstructure of the aluminium alloy.